The application of a mathematical model of sustainability to the results of an environmental impact assessment of the Russeifa landfill, Jordan. (10th December 2012) - Phillips, Jason
The question of whether landfills are or could be sustainable is somewhat unanswered within the sphere of waste management. This is partly due to two key issues: the ambiguities concerning what is sustainability?; and how to effectively assess the potential or actual sustainability of a landfill? It has been argued in the literature that this is a difficult task, however it is not impossible. This paper consequently presents the application of a mathematical model of sustainability to the results obtained for the environmental impact assessment (EIA) of the Russeifa landfill in Jordan using the rapid impact assessment matrix (RIAM) methodology. This paper demonstrates the methodology necessary to apply the model to the RIAM evaluation made at the time of assessment with respect to potential mitigation options. A determination of the level and nature of sustainability (if appropriate) for the project options were obtained for the Russeifa landfill. The results indicated that all of project options evaluated could be considered as unsustainable. This paper concludes by stating that the application of the model to the RIAM analysis offers a potential mechanism in evaluating sustainability through the use of a common and increasingly regarded technique of EIA.